Assessment of Bank Trust in Fishermen Customers to Support the Implementation of the Blue Economy in Situbondo - Ningrum Suryadinata; Achadyah Prabawati; Alifian Rizzalul Ahmad; Jesika Wanda Aprilia (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
The transition of borrowing activities from conventional banks to Rural Banks (BPR) in East Java has contributed to increased credit distribution by BPRs. This study investigates the trust assessment level of Rural Banks in supporting the implementation of the Blue Ocean Economy in Situbondo. Using a descriptive qualitative approach and Blue Ocean Economy concept, the study focuses on fishermen who are BPR customers. Financial soundness is evaluated through key indicators affecting credit distribution, including the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operational Costs to Operational Income (BOPO), and Non-Performing Loans (NPL). The findings reveal that BPR Artha Waringin Jaya has stronger capital adequacy and higher credit distribution than BPR Tridana Kencana. Although both banks operate efficiently, Tridana Kencana records higher operational costs and NPL levels, indicating greater credit risk. Overall, BPRs in Situbondo have the potential to support the Blue Ocean Economy through sustainable credit provision.